86.7k views
5 votes
What is the result of adding these two equations?
62 + 2y = -2
3x - 2y = -5

User Numeri
by
4.8k points

1 Answer

1 vote

Answer:

x = -7/9; y = 4/3.

Explanation:

I will assume that the top equation is 6x + 2y = -2, and the bottom one is 3x - 2y = -5.

If you add the two...

(6x + 3x) + (2y + (-2y)) = (-2 + (-5))

9x + 0 = -7

9x = -7

x = -7/9

6(-7/9) + 2y = -2

-42/9 + 2y = -18/9

2y = 24/9

y = 24/18

y = 12/9

y = 4/3

Hope this helps!

User Marcelofreires
by
5.0k points